'Never think doing a job is easy': The lived experience of work for people who have an intellectual and developmental disability. (November 2022) - Ramsey, Diana; Cameron, Josh; Harrison, Rebecca; Young, Sharon
Introduction: The proportion of people with an intellectual or developmental disability (IDD) in paid employment is low internationally despite policy efforts. Evidence suggests multiple and varied explanations for this, including organisational, social and personal barriers. That evidence has not focused on first-person experiences which may provide a depth of understanding and explanation of the work-related experiences of people with IDD. Method: A hermeneutic phenomenological approach and an exploratory research method of a 'creative collaborative partnership' was adopted to illuminate the work-related experiences of six people with a mild IDD. Findings: Six work stories composed of narratives and visual images were collaboratively created revealing a complex range of positive and negative experiences and perspectives of paid work. Five collective narrative frames emerged: the quest 'to do', navigating bureaucratic seas, finding a good fit, forging of identity and finding both friend and foe. Conclusion: The collaborators' stories highlighted that individuals supporting people with IDD towards or in work, including occupational therapists, need to adopt a nuanced systemic perspective of the context surrounding the person. This includes identifying allies and allowing people with IDD to decide how (if at all) they describe their IDD status to others as they establish their worker identity.